Successful ageing and social support among older people living in the community - Makhtar, Aniawanis (2023)
Background: Successful ageing of older people is influenced by the received social support. As the proportion of older people in Malaysia grows and the need for promoting successful ageing is apparent, it becomes increasingly important to investigate the relationship between successful ageing and social support among older people in the community. Methods: A cross-sectional survey with convenience sampling was conducted on 200 older people living in the community of Kuantan, Pahang. A structured questionnaire, Successful Ageing Inventory and Multidimensional Scale of Perceived Social Support were used to collect data regarding demographics. Data were analysed using IBM SPSS Statistics (version 25). Descriptive statistics, Pearson’s chi-square, and Fisher’s exact test, were used for analysis. The statistical significance level was set at p ≤ 0.05. Results: Most participants were married women living with their spouses or children. The results showed that 98.5% and 75% of older people have highly successful ageing and social support, respectively. A statistically significant relationship was found between successful ageing and social support. However, no significant relationship was observed between successful ageing and demographic characteristics. Conclusion: Successful ageing is influenced by the social support received among older people living in the community. Therefore, implementing intervention programmes on the significant factors to enhance the successful ageing of older people is recommended.